⎩ ⎪ ⎪ ⎨ ⎪ ⎪ ⎧ x sin θ = y cos θ x 4 cos 4 θ + y 4 sin 4 θ = x 3 y + y 3 x 9 7 sin 2 θ
Let x and y be positive real numbers and θ is an angle such that it is not a multiple of 2 π . If x , y and θ satisfy the system of equations above, find y x + x y .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
This is a very very beatiful problem.
So let us see what we have got,
x sin θ = y cos θ
And,
x 4 cos 4 θ + y 4 sin 4 θ = x 3 y + y 3 x 9 7 sin 2 θ
Let us just simplify the second equation,
x 4 cos 4 θ + y 4 sin 4 θ = x 3 y + y 3 x 9 7 sin 2 θ
x 4 y 4 ( x 8 y 4 cos 4 θ + y 8 x 4 sin 4 θ ) = x y ( x 2 + y 2 ) 9 7 ( 2 ) ( sin θ ) ( cos θ )
x 4 y 4 ( x 8 x 4 sin 4 θ + y 8 x 4 sin 4 θ ) = x ( x 2 + y 2 ) 9 7 ( 2 ) ( sin θ ) . y cos θ
sin 4 θ ( x 8 y 4 + y 4 1 ) = x 2 ( x 2 + y 2 ) 9 7 ( 2 ) sin 2 θ
sin 2 θ ( x 8 y 4 y 8 + x 8 ) = x 2 ( x 2 + y 2 ) 9 7 ( 2 )
sin 2 θ = ( x 2 + y 2 ) ( x 8 + y 8 ) 9 7 ( 2 ) x 6 y 4
Similarly,
cos 2 θ = ( x 2 + y 2 ) ( x 8 + y 8 ) 9 7 ( 2 ) x 4 y 6
We know,
sin 2 θ + cos 2 θ = 1
Placing values,
( x 2 + y 2 ) ( x 8 + y 8 ) 9 7 ( 2 ) x 6 y 4 + ( x 2 + y 2 ) ( x 8 + y 8 ) 9 7 ( 2 ) x 4 y 6 = 1
( x 2 + y 2 ) ( x 8 + y 8 ) 9 7 ( 2 ) x 4 y 4 ( x 2 + y 2 ) = 1
9 7 ( 2 ) x 4 y 4 = x 8 + y 8
y 4 x 4 + x 4 y 4 = 1 9 4
y 2 x 2 + x 2 y 2 = 1 4
y x + x y = 4
Truly, the problem is beautiful and would be a delight for algebra lovers.
x sin θ = y cos θ = k
Then, sin θ = x k , cos θ = y k .
Note that sin 2 θ + cos 2 θ = 1. This implies, ( x k ) 2 + ( y k ) 2 = 1 We then obtain, x 2 + y 2 = k 2 1 .
We now substitute the values of sin θ , cos θ in the given equation.
On simplifying, we obtain k 2 ( y 4 x 4 + x 4 y 4 ) = x 2 + y 2 1 9 4 .
Putting the value of k 2 in the above equation, we obtain ( y 4 x 4 + x 4 y 4 ) = 1 9 4 .
Put y 4 x 4 = tan 4 θ = a , x 4 y 4 = cot 4 θ = b . Note that ab =1.
At this stage, we have a 4 + b 4 = 1 9 4 . On observation, we notice that we have to calculate a + b.
Writing ( a 4 + b 4 ) = ( ( a + b ) 2 − 2 a b ) 2 − 2 ( a 2 ) ( b 2 ) = 1 9 4 and putting the value of ab=1 , we obtain ( ( a + b ) 2 − 2 ) 2 = 1 9 6
Put ( a + b ) 2 for T, expand the equation and solve the quadratic so obtained to get the required positive value of T.
Problem Loading...
Note Loading...
Set Loading...
This would definitely reduce some calculations. Substituting y=mx in the second equation, where m=cot θ and cross multiplication gives(along with cancellation of x 4 in denominators): sin 8 θ + cos 8 θ = 1 9 4 sin 4 θ cos 4 θ ⇒ ( sin 4 θ + c o s 4 θ ) 2 = 1 9 6 sin 4 θ cos 4 θ ⇒ sin 4 θ + cos 4 θ = 1 4 sin 2 θ cos 2 θ ⇒ sin 2 θ + cos 2 θ = 4 sin θ cos θ ⇒ tan θ + cot θ = 4 Hence y x + x y = tan θ + cot θ = 4 Beauty of algebra and trigonometry!!